The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1104/pp.51.3.577
|View full text |Cite
|
Sign up to set email alerts
|

Partial Characterization of Cx Cellulase and Cellobiase from Ripening Tomato Fruits

Abstract: Cellulolytic enzymes were studied in extracts from the locular contents of ripening fruits of Lycopersicon esculentum var. KC-146. When acting on carboxymethyl cellulose, the enzyme preparations were capable of decreasing the viscosity of the reaction mixture and generating reducing groups, oligosaccharides, and glucose. Cellobiose celiotriose, celiotetrose, and cellopentose also served as substrates for glucose production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Hobson (7) concluded that cellulase is not a major factor in the softening of tomato fruit during ripening. In studying the cellulase activity of tomato fruits, Pharr and Dickinson (22) found no evidence of the exocellulase activity which initiates enzymatic attack on insoluble cellulose. Most studies of fruit softening have focused on the role of PG' in this process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hobson (7) concluded that cellulase is not a major factor in the softening of tomato fruit during ripening. In studying the cellulase activity of tomato fruits, Pharr and Dickinson (22) found no evidence of the exocellulase activity which initiates enzymatic attack on insoluble cellulose. Most studies of fruit softening have focused on the role of PG' in this process.…”
Section: Methodsmentioning
confidence: 99%
“…The 500 mm Na-citrate extract was the enzyme solution used in assays of activity against all substrates except carboxymethylcellulose. Cellulase was extracted using the method described by Pharr and Dickinson (22 (18).…”
Section: Methodsmentioning
confidence: 99%
“…It allows a determination of [17] from a one point measurement of viscosity: =log[ij] + c X Using relationships (3) and (4), it can be noticed that: ( 9 ) (10) Standard errors are indicated. The difference between CO and CE is without significance.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulolytic enzymes increase in activity in some fruits during ripening (7,9,10,17), in abscission zones of petioles prior to leaf abscission (1,3,12,13), in rapidly expanding epicotyls after auxin treatment (8,16,19), and appear to be involved in pollen tube elongation (22 15), an increase in cellulase activity has been detected only after auxin treatment (16,19,20). The present work provides evidence that in the expanding pea epicotyl, auxin and ethylene each appear to control the development of a different form of cellulase and each enzyme possesses different requirements for activity and apparently differing subcellular locations and isoenzyme complements.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulolytic enzymes increase in activity in some fruits during ripening (7,9,10,17), in abscission zones of petioles prior to leaf abscission (1,3,12,13), in rapidly expanding epicotyls after auxin treatment (8,16,19), and appear to be involved in pollen tube elongation (22). Evidence suggests that more than one molecular form of cellulase (EC 3.2.1.4) may be involved in these diverse physiological plant processes.…”
mentioning
confidence: 99%